Developing an in-service education program for the secondary vocational teachers of the Mindanao Agricultural College - Montemayor, Felicidad (Mananzan) 1905- ([Quezon City s.n.], 1962)
A plan of in-service education program that will meet the demands of the teaching profession was developed in this study. It consists of programs on the two types of vocational teachers - agriculture and home economics - of the secondary department of the Mindanao Agricultural College.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Mindano Agricultural College, Musuan, Bukidnon; Vocational education -- Teacher training